PENYELENGGARAAN KEGIATAN KOPERASI SIMPAN PINJAM YANG BERPOTENSI TINDAK PIDANA PENGGELAPAN DAN PENIPUAN DALAM PASAL 374 JUNCTO 378 KUHP - Nita Julaiyanti (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThis research studies and answers the problem concerning with regulating of holding debit-credit cooperation activity in laws. And also to know potential criminal acts which can be happened in holding debit-credit cooperation activity.This research is a kind of normative and empirical research which is descriptive and observation. The kind of data which is used is secondary data that consist of primary law material, secondary law material and tertiary law material. Data collecting technique used is document study with content analysis technique and data observation.Based on the research and the analyze, it showed that holding the activity of debit-credit cooperation refers to regulation no. 525 1992 about cooperation; Government regulation no. 9 1995 about carrying out of debit credit activity business by cooperation, and the decision of minister of cooperation, little and middle entrepreneur minister of Republic Indonesia no: 351 /KEP/M/XII 1998 about guidance of implementation debit credit activity business by cooperation. From the three regulations which regulate of holding debit credit cooperation activity can be known that debit credit cooperation activity is to unite and to make flow the fund which directed only to the members of cooperation, candidate of member, cooperation and/or its member.Actually at recent time, a lot of debit credit cooperation which unite fund from a broad society beyond members of cooperation. The weak control and even no control against debit-credit cooperation give chance for deviations against regulation regarding with debit credit cooperation. The deviation is directed to criminal acts which make the caretaker and manager of cooperation to be suspected and criminal acts which have potency to be happened in debit-credit cooperation activity are criminal act of embezzlement and fraud. Keywords: Debit-Credit Cooperation, Criminal act.